Fine‐grained material associated with a large sulfide returned from Comet 81P/Wild 2. (4th March 2019) - Gainsforth, Z.; Westphal, A. J.; Butterworth, A. L.; Jilly‐Rehak, C. E.; Brownlee, D. E.; Joswiak, D. J.; Ogliore, R. C.; Zolensky, M. E.; Bechtel, H. A.; Ebel, D. S.; Huss, G. R.; Sandford, S. A.; et al.
Abstract: In a consortium analysis of a large particle captured from the coma of comet 81P/Wild 2 by the Stardust spacecraft, we report the discovery of a field of fine‐grained material (FGM) in contact with a large sulfide particle. The FGM was partially located in an embayment in the sulfide. As a consequence, some of the FGM appears to have been protected from damage during hypervelocity capture in aerogel. Some of the FGM particles are indistinguishable in their characteristics from common components of chondritic‐porous interplanetary dust particles, including glass with embedded metals and sulfides and equilibrated aggregates. The sulfide exhibits surprising Ni‐rich lamellae, which may indicate that this particle experienced a long‐duration heating event after its formation but before incorporation into Wild 2.